Removal of Methyl Orange From Aqueous Solution By Iraqi Bentonite Adsorbent - Al-heetimi, Dhafir T. Ajeel; Dawood, A. H.; Khalaf, Q. Z.; Himdan, T. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The adsorption behavior of methyl orange from aqueous solution on Iraqi bentonite was investigated. The effects of various parameters such as initial concentration of methyl orange, amount of adsorbent, ionic strength and temperature on the adsorption capacity has been studied. The percentage removal of methyl orange increased with the decrease of initial concentration of methyl orange and it increased with the increase of dose of adsorbent. The adsorbed amount of methyl orange decrease with increasing ionic strength and an increase in temperature. The equilibrium adsorption isotherms have been analysed by the linear, Langmuir and Temkin models. The Langmuir isotherms have the highest correlation coefficients. Thermodynamic parameters such as ∆G, ∆H and ∆S for the adsorption process were calculated. The adsorption process was found to be exothermic and spontaneous